Out-of-school digital gameplay and in-school L2 English vocabulary outcomes. (July 2015) - Sundqvist, Pia; Wikström, Peter
Abstract: The aim of the present study is to examine the relation between out-of-school digital gameplay and in-school L2 English vocabulary measures and grading outcomes. Data were originally collected from a sample of 80 teenage Swedish L2 English learners and comprise a questionnaire, language diaries, vocabulary tests, assessed essays, and grades. Using an observational post-hoc design, three Digital Game Groups (DGGs) were created based on frequency of gameplay: (1) non-gamers (0 h/week), (2) moderate gamers (<5 h/week), and (3) frequent gamers (≥5 h/week). Results show that DGG3 had the highest rated essays, used the most advanced vocabulary in the essays, and had the highest grades, closely followed by DGG1, while DGG2 trailed behind. For the vocabulary tests, DGG3 was followed by DGG2 and DGG1, indicating that gameplay aligns more directly with vocabulary test scores than vocabulary indicators drawn from essays. Due to the gender distribution of non-gamers (predominantly girls) and frequent gamers (exclusively boys), a subsidiary aim is to investigate how gameplay correlates with outcomes for boys and girls: significant correlations were found for gameplay–vocabulary tests/English grades for the boys.